TINJAUAN KRIMINOLOGI TERHADAP KETERLIBATAN WANITA DALAM PEREDARAN NARKOTIKA DIHUBUNGKAN DENGAN UNDANG – UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DI KOTA PEKANBARU - Cindy Syafira; Evi Deliana; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This research is in the form of discussing the involvement of women in narcotics circulation. Efforts to illegally distribute narcotics by using people as distribution or courier are often carried out to be able to widely distribute narcotics. This is because the development of Narcotics circulation increasingly shows the variation where in activities that are contrary to the law by involving women to become Narcotics couriers. The problem in this thesis is the factor that causes women's involvement in narcotics distribution and how prevention efforts need to be done to prevent the involvement of women in narcotics distribution and how the application of criminal acts against women as narcotics dealers based on Law Number 35 of 2009 concerning Narcotics.This research uses sociological research. Secondary data was obtained from library research which included literature books, legislation, court decisions, and others. Primary data were obtained directly from research in the field by conducting interviews and questionnaires to informants.Based on the results of research and discussion, it can be concluded that, the form of involvement of women in narcotics circulation is basically as a narcotics courier. Factors that cause women's involvement in narcotics circulation in terms of criminology are: Economic factors, where women make narcotics distribution activities as their livelihoods, environmental factors, educational factors, and factors that lack understanding of the law. Efforts undertaken by the government and law enforcement agencies are: Providing socialization to women about the dangers of narcotics, empowering women in positive activities, and also opening up employment opportunities for women and conducting law enforcement by applying maximum penalties to narcotics dealers. Judicial considerations Judge in imposing a crime against narcotics dealers according to the decision of the Pekanbaru District Court is that the Public Prosecutor's Subsidair is accused of violating the provisions stipulated and threatened with criminal offenses in Article 112 paragraph (1) of the Republic of Indonesia Law No. 35 of 2009 concerning Narcotics.Keywords: Criminology - Women - Crimes – Narcotics